Application of survival analysis to carious lesion transitions in intervention trials - Baelum V, Machiulskiene V, Nyvad B, Richards A, Væth M. (Blackwell Synergy, 2003)
To demonstrate the usefulness of a survival-time regression model for the analysis of data from two 3-year trials of the caries-preventive effect of sugarsubstituted chewing gums and fluoride toothpaste, carried out among 892 Lithuanian children.